Discovery of a potent protein kinase D inhibitor: insights in the binding mode of pyrazolo[3, 4-d]pyrimidine analogues. Issue 3 (15th February 2017) - Verschueren, Klaas; Cobbaut, Mathias; Demaerel, Joachim; Saadah, Lina; Voet, Arnout R. D.; Van Lint, Johan; De Borggraeve, Wim M.
Abstract : Herein we report the synthesis of pyrazolo[3, 4- d ]pyrimidine analogues of 1-NM-PP1 and the identification of 3-IN-PP1 as a new potent PKD inhibitor suggesting an alternate binding mode to PKD. Abstract : In this study, we set out to rationally optimize PKD inhibitors based on the pyrazolo[3, 4- d ]pyrimidine scaffold. The lead compound for this study was 1-NM-PP1, which was previously found by us and others to inhibit PKD. In our screening we identified one compound (3-IN-PP1) displaying a 10-fold increase in potency over 1-NM-PP1, opening new possibilities for specific protein kinase inhibitors for kinases that show sensitivity towards pyrazolo[3, 4- d ]pyrimidine derived compounds. Interestingly the observed SAR was not in complete agreement with the commonly observed binding mode where the pyrazolo[3, 4- d ]pyrimidine compounds are bound in a similar fashion as PKD's natural ligand ATP. Therefore we suggest an alternate binding mode where the compounds are flipped 180 degrees. This possible alternate binding mode for pyrazolo[3, 4- d ]pyrimidine based compounds could pave the way for a new class of specific protein kinase inhibitors for kinases sensitive towards pyrazolo[3, 4- d ]pyrmidines.